2021
DOI: 10.1111/1468-0009.12491
|View full text |Cite
|
Sign up to set email alerts
|

Money Moves the Mare: The Response of Community‐Based Organizations to Health Care's Embrace of Social Determinants

Abstract: Health policies that encourage health and social integration can induce community-based organizations (CBOs) to adopt new ways of working from health care organizations, including their language, staffing patterns, and metrics. These changes can be explained by CBOs' perceptions that health care organizations may provide new sources of revenue. r While the welfare implications of these changes are not yet known, policymakers should consider balancing the benefits of professionalizing CBOs against the risks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Information on the perspectives of all 3 of these stakeholder groups is scarce, and yet the active involvement of each is essential for successful interventions to address FI in health care settings. 23 In this article, we share findings regarding multistakeholder perspectives on data sharing for the purposes of FI screening and referral in primary care settings located in rural and smaller town locations.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the perspectives of all 3 of these stakeholder groups is scarce, and yet the active involvement of each is essential for successful interventions to address FI in health care settings. 23 In this article, we share findings regarding multistakeholder perspectives on data sharing for the purposes of FI screening and referral in primary care settings located in rural and smaller town locations.…”
Section: Introductionmentioning
confidence: 99%
“…CBOs may not necessarily have previously needed to provide evidence of the population health or financial impact of their services to medically oriented health care entities. CBOs are, in fact, charitable organizations that are quite separate from a profitoriented business model or the layers of government regulations that MA plans face, and have their own ethical and legal standards which MA plans may not be familiar with (Taylor & Byhoff, 2021). A recent qualitative study of CBO representatives found that CBOs value and seek to maintain their distinct missions and community focus, but financial incentives lead some CBOs to make organizational changes to better match the structure of health care organizations (Taylor & Byhoff, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…CBOs are, in fact, charitable organizations that are quite separate from a profitoriented business model or the layers of government regulations that MA plans face, and have their own ethical and legal standards which MA plans may not be familiar with (Taylor & Byhoff, 2021). A recent qualitative study of CBO representatives found that CBOs value and seek to maintain their distinct missions and community focus, but financial incentives lead some CBOs to make organizational changes to better match the structure of health care organizations (Taylor & Byhoff, 2021). Moreover, recognition of the importance of addressing social needs, along with the rise in value-based care, has only recently expanded opportunities for meaningful cross-sector collaboration that requires traversing of these organizational differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 To participate in these efforts and support partnerships with health care organizations, it is important for CBOs to build evaluation capabilities both to guide their own efforts as well as to demonstrate to funders and other stakeholders that they are effectively implementing evidence-based interventions. 9 Research suggests that building evaluation capacity, or the ability to perform evaluations, requires CBOs and their staff to buy into the importance of evaluation, commit sufficient resources to collect data, and collaborate with external researchers to develop sustainable evaluation methods. [10][11][12][13] Previous efforts to strengthen internal evaluation capacity have centered on providing CBOs with onsite technical assistance, developing evaluation skills through training programs, and offering interactive web-based systems to guide evaluation design.…”
Section: Introductionmentioning
confidence: 99%